The Effect of Compound Training in Some Physical Abilities and Accuracy of Scoring for the Free Kick of Direct Young Football Players - Qassem Mohammed Hassan (Journal of Global Pharma Technology, 2018)
As the importance of research in the preparation of complex exercises and knowledge of the impact on some physical abilities and accuracy of the skill of scoring for the free kick directly to the football of young players. The problem of research: researchers believe that the problem of research is concentrated in the lack of use of trainers for physical training exercises that participate directly in the free kick direct football. Therefore, the researchers considered the preparation of complex exercises (physical and professional) which would affect some physical abilities contributing to the accuracy of scoring free kick direct football, so researchers wanted to go into this experiment.Research ObjectivesPreparation of training exercises for football.Knowing the effect of the combined exercises in some physical abilities contribute to the accuracy of scoring for the direct free kick of young football players.Research HypothesisThere is an impact of the training complex in some physical abilities of young football players.The impact of the training of the vehicle in the accuracy of direct free kick score among young football players.As for the research methodology and field procedures, researchers used the experimental method to solve the problem of research. The research community was identified by the young players of Najaf clubs for the season 2017-2018, which are 8 players who are skilled in the free kick. And control) in a simple random way (lots).As for the most important conclusions and recommendations, the most important conclusions are the following:The complex exercises helped to develop some of the physical abilities of (explosive power, the power of speed, speed motor).The complex exercises contributed to the development of the accuracy of scoring free kick direct to football.Keywords: Compound training, physical abilities and accuracy of scoring.